ELABORATION AND PHYSICAL-CHEMICAL AND SENSORIAL CHARACTERIZATION OF DRIED BANANA FLAVORED WITH SPICES - Souza, Alissandra de Oliveira; Souza, Rosane Liege Alves de; Oliveira, Emanuel Neto Alves de; Piovesan, Natieli (ENERGIA NA AGRICULTURA, 2021)
ELABORATION AND PHYSICAL-CHEMICAL AND SENSORIAL CHARACTERIZATION OF DRIED BANANA FLAVORED WITH SPICES ALISSANDRA DE OLIVEIRA SOUZA1, ROSANE LIÉGE ALVES DE SOUZA2, EMANUEL NETO ALVES DE OLIVEIRA3, NATIELI PIOVESAN4 1 Instituto de Educação, Ciência e Tecnologia do Rio Grande do Norte, BR 405, Km 154, Chico Cajá, 59900-000, Pau dos Ferros, RN, Brasil, alissandraoliveira16@gmail.com. 2 Departamento de Gastronomia, Universidade Federal da Paraíba, Rua dos Escoteiros, s/n - Mangabeira, 58058-600, João Pessoa, PB, Brasil, rosaneliege@yahoo.com.br. 3 Instituto de Educação, Ciência e Tecnologia do Rio Grande do Norte, BR 405, Km 154, Chico Cajá, 59900-000, Pau dos Ferros, RN, Brasil, emanuel.oliveira16@gmail.com. 4 Instituto de Educação, Ciência e Tecnologia do Rio Grande do Norte, BR 405, Km 154, Chico Cajá, 59900-000, Pau dos Ferros, RN, Brasil, natieli.piovesan@ifrn.edu.br. ABSTRACT: Brazil is the fifth largest producer of banana. However, there are significant losses due to transportation and its high perishability and. The osmotic dehydration followed by drying can add value to the product, reduce transportation costs, decrease the acidity, and heighten the taste of the original fruit. Therefore, the work aimed to elaborate dried banana using osmotic dehydration followed by drying, flavored with spices, and to evaluate the physical-chemical and sensorial characteristics. The fresh and flavored bananas were submitted to the physical-chemical analysis. The final product also underwent a sensory evaluation. The water content parameter was according to the legislation for dehydrated fruit. The water activity of the treatments decreased compared to the fresh product, favoring the conservation at room temperature. The reducing sugars increased and were entirely accounted for in the dried banana seasoned with clove and cinnamon. Treatments with clove and fennel were accepted for the attributes of appearance, color, and firmness, but did not present sensory characteristics superior to traditional bananas. Only the dried banana flavored with cinnamon-presented acceptability index higher than 70% for the flavor attribute. However, it is worth noting that this refers to the new food with a peculiar taste. Keywords: Pacovan, flavorization, osmotic dehydration. ELABORAÇÃO E CARACTERIZAÇÃO FÍSICO-QUÍMICA E SENSORIAL DE BANANA PASSA SABORIZADA COM ESPECIARIAS RESUMO: O Brasil é o quinto maior produtor de banana, porém as perdas pela alta perecibilidade e transporte são significativas. A desidratação osmótica seguida de secagem, pode agregar valor, reduzir custos com transporte, diminuir a acidez e elevar o sabor da fruta original. Desta forma, o objetivo do trabalho foi elaborar bananas passa por desidratação osmótica seguida de secagem, saborizadas com especiarias e avaliar as características físico-química e sensoriais. A banana in natura e as saborizadas foram submetidas a análises físico-químicas. O produto final também passou por avaliação sensorial. A umidade concordou com a legislação para fruta desidratada, já a atividade de água diminuiu do produto in natura para os tratamentos, favorecendo a conservação a temperatura ambiente. Já os açúcares redutores se elevaram, sendo totalmente contabilizados na banana passa com cravo-da-índia e canela. Os tratamentos com cravo-da-índia e erva-doce foram aceitos nos atributos de aparência, cor e firmeza, porém não apresentaram características sensoriais superiores a banana passa tradicional. Apenas a saborizada com canela teve índice de aceitabilidade maior do que 70% para o atributo sabor. No entanto, vale salientar que refere-se a alimento novo com sabor peculiar. Palavras-chave: Pacovan, saborização, desidratação osmótica.